CONCEPTUAL PAPER: THE IMPACT OF INTERCULTURAL COMMUNICATION COMPETENCE ON UNIVERSITY STUDENTS’ ENGLISH LANGUAGE LEARNING MOTIVATION IN JIANGXI, CHINA - Liu Ping; Wong Siew Ping (Journal of Islamic, Social, Economics and Development, 2024)
In an era of globalization, where cultural diversity and cross-cultural interactions are increasingly prevalent, the ability to communicate effectively across cultures is paramount. English language learning motivation among students in Jiangxi, China, faces significant challenges. Students often perceive English language as a daunting subject due to its complex grammar rules and unfamiliar cultural contexts. Moreover, the lack of exposure to authentic English language -speaking environments and limited opportunities for meaningful interactions with native English language speakers contribute to a decrease in students' motivation to learn the language. Notably, traditional educational methods in China often emphasize rote memorization and exam-oriented learning, hindering students' ability to engage in innovative intercultural communication. Students with a higher degree of intercultural communication competence (ICC) tend to approach English not just as a linguistic tool, but as a gateway to understanding and engaging with a global community. Their competence in navigating cultural nuances and differences enhances their confidence in real-world interactions, thereby increasing their motivation to learn and master the language. Past research uncovers that students with higher ICC tend to exhibit greater motivation for English language learning. This concept paper aims to explore the impact of ICC on university students' motivation for English language learning. It was proposed to employ a cross-sectional survey design, collecting data from a representative sample of Chinese university students majoring in English language. The survey assesses their ICC levels and motivation to enhance their English language skills. Findings will be analyzed quantitatively. Descriptive analysis and inferential analysis such as correlation analysis, and multiple regression tests will be conducted. The study's findings hold theoretical significance by contributing to the existing body of knowledge on ICC and its link to language learning motivation. Additionally, it offers practical implications for educators and policymakers in Jiangxi, China, before considering the need for reform in English language teaching methods and curricula to foster ICC and intrinsic motivation among students. In a globalized world, enhancing ICC is vital for successful cross-cultural interactions, and this study sheds light on its pivotal role in motivating students to excel in English language learning, ultimately contributing to their personal growth and the development of a more inclusive society in Jiangxi, China.